2008
DOI: 10.1089/neu.2008.0554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rosuvastatin on Amnesia and Disorientation after Traumatic Brain Injury (NCT00329758)

Abstract: Amnesia is a common sequela following traumatic brain injury (TBI), for which there is no current treatment. Pleiotropic effects of statins have demonstrated faster recovery of spatial memory after TBI in animals. We conducted a double-blind randomized clinical trial add-on of patients with TBI (16-50 years of age), with Glasgow Coma Scale (GCS) scores of 9-13, and intracranial lesions as demonstrated by computed tomography (CT) scan. We excluded those patients with recent head injury or severe disability; adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 25 publications
0
54
0
1
Order By: Relevance
“…[12][13][14][15] All had placebo rather than standard care comparators. RCTs (reported in 23 publications [13][14][15][36][37][38][39][40][41][42][43][44][45][46][47][48][50][51][52]55,56,62,64 ) enrolled subjects with normal cognition at baseline, four RCTs (reported in seven publications 12,54,[57][58][59][60][61] ) enrolled patients with AD, and three RCTs enrolled other cognitively impaired subjects (traumatic brain injury, 53,63 and neurofibromatosis type 1 49 ). Simvastatin (eight trials), pravastatin (eight trials), and lovastatin (six trials) were most frequently utilized in the statin RCTs.…”
Section: Assessment Of Heterogeneity and Meta-regression Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] All had placebo rather than standard care comparators. RCTs (reported in 23 publications [13][14][15][36][37][38][39][40][41][42][43][44][45][46][47][48][50][51][52]55,56,62,64 ) enrolled subjects with normal cognition at baseline, four RCTs (reported in seven publications 12,54,[57][58][59][60][61] ) enrolled patients with AD, and three RCTs enrolled other cognitively impaired subjects (traumatic brain injury, 53,63 and neurofibromatosis type 1 49 ). Simvastatin (eight trials), pravastatin (eight trials), and lovastatin (six trials) were most frequently utilized in the statin RCTs.…”
Section: Assessment Of Heterogeneity and Meta-regression Analysesmentioning
confidence: 99%
“…One showed no statistically significant cognitive benefit over 6 months, 53 and the other showed positive benefit over 4 months. 63 A small trial of 62 children with neurofibromatosis type 1, expected to have a high prevalence of learning disability, showed no significant effects for statin treatment. 49 …”
Section: Studies Of Cognitively Normal Participantsmentioning
confidence: 99%
“…19−21 Rosuvastatin in a small clinical trial in patients with moderate TBI improved amnesia; however, it showed no differences in 3-month outcomes. 22 This may be due to the inability of the hydrophilic rosuvastatin to enter the brain. 23 Progesterone has shown neuroprotective effects in animal models of spinal cord injury, stroke and TBI, 24−26 and has shown possible signs of benefit in clinical trials in patients after TBI.…”
mentioning
confidence: 99%
“…No difference was found between the groups in the median IL-1␤ or TNF-␣ levels; in fact, contrary to animal models, median IL-6 levels were increased in the statin-treated group. 25 However, it is worth noting that rosuvastatin has limited CNS penetration, and thus it is difficult to draw definitive conclusions for the effect of statins on CNS inflammation based on of this small pilot study.…”
Section: Effects On Inflammation and Excitotoxicitymentioning
confidence: 90%
“…Of importance, the authors note that the rosuvastatin group had a somewhat worse degree of TBI at baseline than the placebo group. 25 After preclinical data suggesting neuroprotection, statins have also been considered in other forms of acute brain injury commonly associated with TBI. Clinical data on statins in ICH is mixed.…”
Section: Clinical Experience With Statins For the Treatment Of Acute mentioning
confidence: 99%